Elective Venovenous Extracorporeal Membrane Oxygenation for Resection of Endotracheal Tumor: A Case Report. Issue 4 (15th August 2017) - Dunkman, W. Jonathan; Nicoara, Alina; Schroder, Jacob; Wahidi, Momen M.; El Manafi, Aimen; Bonadonna, Desiree; Giovacchini, Coral X.; Lombard, Frederick W.
Abstract : We present a case in which we electively used venovenous extracorporeal membrane oxygenation (VV-ECMO) to facilitate safe resection of a nearly obstructing airway tumor near the carina in a 37-year-old male. The patient was brought to the operating room and underwent bifemoral cannulation for VV-ECMO under light sedation while maintaining spontaneous ventilation. After VV-ECMO was initiated, general anesthesia was induced, and the tumor was resected via rigid bronchoscopy. After resection, the patient was intubated, weaned from ECMO, decannulated, awoken, extubated, and taken to the postanesthesia care unit for recovery.